Dietary intake and cardiovascular disease risk factors among nutrition and dietetics degree students in UiTM Puncak Alam / Nur Shamin Hamalis Mokhtaridi - Mokhtaridi, Nur Shamin Hamalis (2016)
Dietary intake can affect individual health status. Most of non-communicable disease (NCD) are due to unhealthy food habit. A lot of studies were done to find the correlation between dietary intake and cardiovascular disease (CVD) risk factors among adults. However, less study about the dietary intake and CVD risk factors among young adult. Thus, this cross-sectional study is conducted to assess dietary intake and CVD risk factors among Nutrition and dietetics students in UiTM Puncak Alam. A total of 123 students aged between 19 to 24 years old both female and male have participated in this study. There are four assessments conducted in this study which are anthropometry, biochemical, clinical and dietary assessment. Weight, height and waist circumference of the participant were taken for anthropometry assessment. While, for biochemical assessment fasting blood glucose and total cholesterol were assessed. Blood pressure and body fat percentage are taken for the clinical assessment. Last but not least, questionnaire consist of 165 item food frequency questionnaire and socio-demographic questions were distributed to all participants. Most of the participant were female which 114 is (92.7%). The median frequency of fruit and vegetable is low compared to recommend frequency which is three and six respectively. Next, the median serving size of vegetable is two below than recommended serving which is three. Only 34.1% of the participant take vitamin and mineral supplements. White rice is the most frequent food that is consumed daily with mean frequency 1.50 ± 0.58 by 93.5% of the participants. The majority of the participants have the normal body mass index (BMI) and percentage of body fat. Next, for the prevalence of CVD risk factors, BMI more than 24.9 kg/m2 (22.8%) has the highest prevalence and family history of hypertension (43.9%) is the most prevalence among the participants compared to other diseases. Last but not least, only three food item give correlation to CVD risk factor. However, it is a poor correlation. The food item that give correlation is white rice, chili and condiment. Further study needs to be done in order to find out the correlation between white rice, chili and condiment with CVD risk factor.